José Filgueira Valverde (1928-1976): And his experience as a humanist teacher - Torres de Aboal, Germán Manuel (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Given José Filgueira Valverde’s education, convictions, and life trajectory, he is nowadays a paradigm in education and humanist teacher. He taught within the framework of Christianity in the Institute of the city of Pontevedra (1939-1976). His work made him one of the most influential people of Pontevedra in his time. Family, teachers, and friends influenced him during his entire career. Besides, José Filgueira Valverde (1906-1996) was training in social sciences. His academic education had a high impact on his teaching practices at the Institute of Spanish Language and Literature (1928-1976).